2014
DOI: 10.1016/j.scitotenv.2014.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and temporal variations of water-soluble dicarboxylic acids and related compounds in aerosols from the northern vicinity of Beijing: Implication for photochemical aging during atmospheric transport

Abstract: Abstract:Aerosol samples were collected in autumn 2007 on day-and nighttime basis in the northern receptor site of Beijing, China. The samples were analyzed for total carbon (TC) and water-soluble dicarboxylic acids (C 2 -C 12 ), oxocarboxylic acids (C 2 -C 9 ), glyoxal and methylglyoxal to better understand the photochemical aging of organic aerosols in the vicinity of Beijing. Concentrations of TC are 50% greater in daytime when winds come from Beijing than in nighttime when winds come from the northern fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…The average temperature and relative humidity at Mangshan were 25 C and 57% in daytime and 17 C and 78% in nighttime. The dominant wind pattern was characterized by southwesterly wind (205 , on average) during daytime and northeasterly wind (30 , on average) during nighttime, being consistent mostly with air mass back trajectories (He et al, 2014). Rainfall was observed at night of September 17, evening of September 26, and daytime of Oct 1.…”
Section: Site Description and Aerosol Samplingsupporting
confidence: 56%
See 2 more Smart Citations
“…The average temperature and relative humidity at Mangshan were 25 C and 57% in daytime and 17 C and 78% in nighttime. The dominant wind pattern was characterized by southwesterly wind (205 , on average) during daytime and northeasterly wind (30 , on average) during nighttime, being consistent mostly with air mass back trajectories (He et al, 2014). Rainfall was observed at night of September 17, evening of September 26, and daytime of Oct 1.…”
Section: Site Description and Aerosol Samplingsupporting
confidence: 56%
“…Another possibility may be a large production of SOA by photochemical processing during the transport from the industrial area of Beijing to Mangshan site in daytime. Interestingly, He et al (2014) reported increased concentrations of dicarboxylic acids, which may serve as markers of photochemical production, and related compounds in daytime during the same campaign. The production of dicarboxylic acids and related compounds in photochemical process should contribute to the increase of OC/EC ratios in daytime.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Except for ωC 7 and ωC 8 , the oxoacids showed larger concentrations in cold seasons (autumn and winter), which might be attributed to accumulation under stagnant meteorological conditions. Their concentrations were higher than those in aerosols from Tanzania (60.0 ± 19.0 and 31.0 ± 18.0 ng m −3 in PM 2.5 during dry and wet seasons, respectively; Mkoma and Kawamura, 2013) but much lower than these detected in Mangshan, a rural site in Beijing (159 ng m −3 in the daytime, 97.9 ng m −3 in the nighttime; He et al, 2014).…”
Section: W Zhao Et Al: Seasonal Variation In and Molecular Distribumentioning
confidence: 70%
“…Some ozone data from regional GAW sites and Chinese EPA site have been reported (Chan et al 2002;Cheung and Wang 2001;Wang et al 2001Wang et al , 2006Zhu et al 2004). In the recent years, however, more data and analysis from both long-term and intensive campaign studies in China became available (Gao et al 2005;He et al 2014;Kanaya et al 2009Kanaya et al , 2013Li et al 2008;Lin et al 2008Lin et al , 2011Meng et al 2009;Xu et al 2008Xu et al , 2011.…”
Section: Introductionmentioning
confidence: 99%